(untitled) (Salduie, 2025)
Deimatism is a behaviour that has had special relevance in our evolutionary history. In this article we analyse ocular deimatism in relation to prehistoric graphies. We will analyse the expressions of fear in Palaeolithic facial graphies, the ’ocellated’ spots of the ’Licorne’ of Lascaux, the dangerous attributes in feline graphies, the gaze of the ’sorcerer’ of Trois-Frères and the hidden ’idols’, under a new biological and neurological perspective. We will also discuss the use of ter-minology in order to better understand the graphic repertoire bequeathed by our ancestors.